A pilot study of risk factors in cleft lip/palate patients in Kelantan - Ismail, Abdul Rashid Haji; Ismail, Noorliza Mastura; Naing, Lin; Rowi, Rowani Mohd (2003)
About 2-3% of pregnancies result in neonates with serious genetic diseases or birth defects causing disabilities, mental retardation, and in some cases early death. Non-syndromic cleft lip and palate (CLP) is a common craniofacial anomaly affecting between lin 700 and 1 in 1000 births in the UK and USA respectively. In Malaysia, studies of school children showed the incidence of 1 in every 941 subjects examined. The risks of non-syndromic cleft lip with or without cleft palate and isolated cleft palate (CLP) are influenced by variations at several loci of the gene and these loci interact with environmental factors to determine disease risk.The aim of the study is to establish the relationship between risk factors and incidence of cleft lip and palate and further enhance research activities in finding specific genetic factors that are sensitive to the risk factors.This is a case controlled study of non-syndromic CLP patients attending combined clinic in Kota Bharu and patients attending outpatient clinic in HUSM. Information was obtained by interviewing parents using questionnaires. Patients attending CLP clinic were first interviewed. The age of the control group was restricted to age. Univariate and multiple logistic regression analysis were used to analyze the data.More than 90% of the subjects are Malays from lower socio-economic status. It was found that demographically there are variations to risks of non-syndromic CLP. People from Tanah Merah and Tumpat are 8.74 fold increase risk compared to people from Kota Bharu. There is association between passive smokers and CLP(OR)= 2.45(95% CI: 1.5,3.94). Maternal and paternal history of cleft, occupation of father and position of child in the family increase the risk of CLP (p=0.009).The study suggested that there are some geographical variations in the risk of CLP. Copper et al (2000) believed that the variation could indicate environmental factors such as seasonal availability of nutrients, infectious disease circle and vitamin deficiency during pregnancy. Exposure to cigarette smoke (passive smokers) is shown to increase the risk of CLP. This is consistent with the findings of Wyszynski et al (1997).The seventh child and above have increased risk of CLP. This could be due to increased maternal age as consistently in other studies.This analysis suggests a small but statistically significant association between maternal cigarette smoking during the first trimester of gestation and increased risk of having child with CLP.